Comparison of State-owned and private emerging market enterprises’ (EMEs) internationalization: case studies of Chinese state-owned and private automobile enterprises’ cross-border acquisitions. - Wang, Si (2013)
This research examines the internationalization behaviors of firms from emerging markets. Through adopting the framework of the three pillars of institutions and integrating the traditional theories with the institution-based view in explaining the international expansions of firms from emerging markets, the study enables us to compare the different roles that institutional drivers play in state-owned emerging market enterprises (EMEs) and private EMEs’ internationalization as well as the different motives for their cross-border expansions. Some challenges for these two types of firms’ international expansions can also be drawn based on the discussions.